Stem Cell Ophthalmology Treatment Study (SCOTS) for retinal and optic nerve diseases: a preliminary report - Jeffrey N Weiss (Neural Regeneration Research, 2015)
In this report, we present the results of a single patient with optic neuropathy treated within the Stem Cell Ophthalmology Treatment Study (SCOTS). SCOTS is an Institutional Review Board approved clinical trial and is the largest ophthalmology stem cell study registered at the National Institutes of Health to date- www.clinicaltrials.gov Identifier NCT 01920867. SCOTS utilizes autologous bone marrow-derived stem cells in the treatment of optic nerve and retinal diseases. Pre- and post-treatment comprehensive eye exams were independently performed at the Wilmer Eye Institute at the Johns Hopkins Hospital, USA. A 27 year old female patient had lost vision approximately 5 years prior to enrollment in SCOTS. Pre-treatment best-corrected visual acuity at the Wilmer Eye Institute was 20/800 Right Eye (OD) and 20/4,000 Left Eye (OS). Four months following treatment in SCOTS, the central visual acuity had improved to 20/100 OD and 20/40 OS.